Field Investigation of a New Recharge Approach for ASR Projects in Near‐Surface Aquifers. Issue 3 (27th August 2015) - Liu, Gaisheng; Knobbe, Steven; Reboulet, Edward C.; Whittemore, Donald O.; Händel, Falk; Butler, James J.
Abstract: Aquifer storage and recovery (ASR) is the artificial recharge and temporary storage of water in an aquifer when water is abundant, and recovery of all or a portion of that water when it is needed. One key limiting factor that still hinders the effectiveness of ASR is the high costs of constructing, maintaining, and operating the artificial recharge systems. Here we investigate a new recharge method for ASR in near‐surface unconsolidated aquifers that uses small‐diameter, low‐cost wells installed with direct‐push (DP) technology. The effectiveness of a DP well for ASR recharge is compared with that of a surface infiltration basin at a field site in north‐central Kansas. The performance of the surface basin was poor at the site due to the presence of a shallow continuous clay layer, identified with DP profiling methods, that constrained the downward movement of infiltrated water and significantly reduced the basin recharge capacity. The DP well penetrated through this clay layer and was able to recharge water by gravity alone at a much higher rate. Most importantly, the costs of the DP well, including both the construction and land costs, were only a small fraction of those for the infiltration basin. This low‐cost approach could significantly expand the applicability of ASR as a water resources management tool to entities with limited fiscal resources, such as many small municipalities and rural communities. The results of this investigation demonstrate the great potential of DP wells as a new recharge option for ASR projects in near‐surface unconsolidated aquifers.